TINJAUAN SISTEMATIK: META-SINTESIS FAKTOR SOSIAL BUDAYA YANG MEMPENGARUHI GAYA HIDUP REMAJA - Salma Talitha; Tri Krianto Karjoso Karjoso (Universitas Pahlawan, 2022)
Lifestyle of adolescent was the main factor predicting health quality of a community. It was necessary to consider several aspects, including socio-cultural aspects, in deciding an intervention promoting health lifestyle among adolescent. The aim of this study was to synthesize socio-cultural factors influencing lifestyle as a basic concept to deliver health promotion among adolescent. This study use qualitative: meta synthesis with meta ethnography method. Article sample was collected from online databases: Science Direct, ProQuest, Scopus, dan SpringerLink. Sample quality was assessed using Critical Appraisal Skills Program (CASP) for qualitative research. Adolescent lifestyle was determined by variations of socio-cultural factors. Body image, financial resources, family culture, and peer influence were strong factors in influencing lifestyle among adolescent. Meanwhile, the conditions of school environment and neighborhood were physical environmental factors that influenced adolescent decision to choose healthy lifestyle. Considering the socio-cultural aspects in predicting lifestyle among adolescent was important. Developing a positive body image, empowering family members, and modifying physical environment could be done as part of an intervention promoting healthy lifestyle among Indonesian adolescent. Keywords : adolescent, lifestyle, socio-cultural